Consequences of "greenwashing". Issue 6 (10th August 2015) - Rahman, Imran; Park, Jeongdoo; Chi, Christina Geng-qing
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This quasi-experimental study aimed to investigate, drawing upon influential discounting behavior theory and cognition – affect – behavior (C-A-B) paradigm, consumers' reactions to the phenomenon of "greenwashing" in the lodging industry. More specifically, this paper proposed and tested a theoretical model that examined whether recognizing the ulterior motive caused consumer skepticism about hotels' environmental claims, which in turn influenced consumers' intention to participate in linen reuse program and intention to revisit the hotel. Additionally, the moderating effects of ecological concern on the relationship between skepticism and intention to participate and between skepticism and intention to revisit were examined. Design/methodology/approach – A quasi-experimental design was used with two conditions (control vs ulterior motive) employing staff members of a US public university as study participants. In total, 638 useful responses were received. Findings – The results of this study revealed that an ulterior motive of hotels' environmental claims evoked consumer skepticism, which, in turn, negatively influenced consumers' intention to participate in the linen reuse program and intention to revisit the hotel. Skepticism was found to partially mediate the relationships between ulterior motive and intention to participate and between ulterior motive and intention to revisit. Consumers' ecological concern was not found to moderate the relationship between skepticism and intention to participate in the linen reuse program and skepticism and intention to revisit the hotel. In addition, a significant positive direct effect between ecological concern and intention to participate and a non-significant effect between ecological concern and revisit intention were revealed. Research limitations/implications – Focus on consumers' response to the ulterior motive of environmental claims advances an understanding of consumers' attitudes and perceptions about hotels' green practices. Practical implications – Findings suggest that hotels need to be watchful so that consumers do not become skeptical. Therefore, it is of utmost importance that managers do everything possible to give customers no room for doubt. Hoteliers need to spend more effort in installing comprehensive green programs and make true green claims by keeping the potential consequences of greenwashing in mind. Hoteliers also need to seek out third-party certifications that require the hotel to meet certain standards, which will help ensure credibility in the eyes of consumers. Originality/value – Hospitality literature has seldom explored this gray area of green marketing, and, in this regard, this study serves as a guide to hoteliers and researchers alike. The authors thereby anticipate that this study would encourage more research in this often overlooked but highly important area.